Impact of ocean acidification and warming on the early ontogeny of a tropical shark - Pegado, Maria Rita de Carvalho Godinho Macedo (2014)
Tese de mestrado. Biologia (Ecologia Marinha). Universidade de Lisboa, Faculdade de Ciências, 2013